Age and Opportunistic Infections: Prevalence and Predictors among Older People Living With HIV - Shivangi A Inamdar; J K Kosambiya; Anjali Modi; Alpesh Gohil; Alap Mehta; Tinkal Patel (Medsci Publications, 2018)
Objectives: To document prevalence of opportunistic infections (OI) among older people living with HIV and to assess predictors of opportunistic infections among older people living with HIV. Methods: A retrospective cohort study was conducted on records of 190 alive older people living with HIV (PLHIV) aged 50 years or more on ART at ART centre, New Civil Hospital, Surat. Socio- demographic variables, WHO stage, CD4 count and OIs were studied. Statistical analysis: Data was analysed by SPSS software to calcu- late frequencies and measures of central tendencies. Logistic Re- gression model was applied. Results: Participants mean age was 57.89 ±5.45 years, 66.84% were males. Heterosexual route was major route of HIV transmission. Prevalence of OIs was 63.7%; with Tuberculosis 22.1% most com- mon, followed by ARI 17.2% and Oral candidiasis 13.2%. Baseline WHO clinical stage III (OR: 8.2; CI: 2.873-23.870) and IV (OR:21.7; CI: 3.83-122.90), Baseline CD4 <200 cells/cumm (OR:3.7; CI:1.10-12.11), weight <50kg in last visit (OR:2.9; CI: 1.07-8.23)were predic- tors of OIs among older PLHIV. Conclusion: Low CD4 count and higher stage of disease at initia- tion of ART, weight <50kg in last visit are predictors for OI by Lo- gistic Regression model